Linguistic Taboo in Romanian Poetry. Trauma, Depression and Addictions - Alina NECULACHI (ACROSS)
This paper aims to analyse the linguistic taboo in contemporary Romanian poetry, interpreting the euphemisms and dysphemisms related to traumatic experiences, depression and addictions, which function as tabooed realities at the level of the poetic discourse.